ADDITION PRODUCT OF IRON(II) COMPLEX OF AROMATIC DIIMINE WITH SULPHURIC ACID - Khattak, Rozina; Naqvi, Iftikhar Imam (Journal of Research (Science), 2025)
Tris(2,2′-bipyridine) iron(II) cation was identified by the methods like Job’s continuous variation, slope ratio and mole ratio. Stability constant of the complex ion was established with the help of Job’s continuous variation method. Sulphate salt of the complex ion in the form of addition product with sulphuric acid of the type [Fe(bipy)3]SO4. 4H2O.H2SO4 was crystallized out and characterized by different techniques like elemental analysis, IR-spectroscopy, pH-metry and UV-Visible absorption spectrophotometry. The data suggests a 1:1 ([Fe(bipy)3]SO4.4H2O : H2SO4) stoichiometry for the addition product. It was also found that aqueous solution of the addition product shows acidic behavior due to the presence of H2SO4. Other characteristics like wavelength maximum, molar extinction coefficient and stability of [Fe(bipy)3]SO4.4H2O.H2SO4 were spectrophotometrically established.